Misleading Equation: City Brandings, Stadiums, Concerts and Neighbours...? The Case of the Santiago Bernabeu Stadium - Lavín, José M.; Jiménez-Sánchez, Álvaro (Street Art & Urban Creativity, 2025)
The need of cities to improve their positioning has found in football clubs, which are economically strapped, some very suggestive allies, since the use of the teams’ infrastructures for purposes other than sporting ones, such as holding concerts, is part of an equation that favours both the strengthening of the City Brand and the increase in income for the clubs. The relationship between the cities and the teams and their facilities has then been studied as to how they manage, at least in theory, to contribute to the City Brand. However, the problem caused by the remodelling of the Santiago Bernabéu stadium and the continuous programming of concerts has seriously affected the habitability of the neighbourhood. Not only has the proposed equation not been fulfilled, but it seems to be lowering the quality of life of those affected by the collision between the intended economic development and the habitability of the neighbourhood where the football club’s identity is based.